2022
DOI: 10.1038/s44161-022-00091-z
|View full text |Cite
|
Sign up to set email alerts
|

The Complementary Value of Absolute Coronary Flow in the Assessment of Patients with Ischaemic Heart Disease

Abstract: Fractional flow reserve (FFR) is the current gold standard invasive assessment of coronary artery disease (CAD). FFR reports coronary blood flow (CBF) as a fraction of a hypothetical and unknown normal value. Although used routinely to diagnose CAD and guide treatment, how accurately FFR predicts actual CBF changes remains unknown. In this study, we compared fractional CBF with absolute CBF (aCBF, in ml min−1), measured with a computational method during standard angiography and pressure wire assessment, on 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Clinically, the patient cohort for which absolute Q assessment will be of value and thresholds for intervention are currently unknown and subject to ongoing research. 30 Fournier et al have previously reported a difference in hyperaemic LAD flow between healthy and mildly disease arteries of 65 mL/min. 27 Given the reported error in the current study, at the current stage of development, virtuQ assessment of absolute Q in minimally diseased arteries may be of limited clinical utility.…”
Section: Discussionmentioning
confidence: 94%
“…Clinically, the patient cohort for which absolute Q assessment will be of value and thresholds for intervention are currently unknown and subject to ongoing research. 30 Fournier et al have previously reported a difference in hyperaemic LAD flow between healthy and mildly disease arteries of 65 mL/min. 27 Given the reported error in the current study, at the current stage of development, virtuQ assessment of absolute Q in minimally diseased arteries may be of limited clinical utility.…”
Section: Discussionmentioning
confidence: 94%
“…Further exclusion criteria for all cases included ST-segment elevation myocardial infarction within the preceding 60 days, any contraindication to adenosine or contrast media, previous coronary artery bypass surgery, patient age below 18 years, chronic total occlusion, severe valvular disease and an inability to consent. This was a post hoc analysis of the Complementary Value of Absolute Coronary Flow in the Assessment of Patients with Ischaemic Heart Disease (the COMPAC-Flow) study ( 12 ), in which computational fluid dynamics- (CFD-) derived absolute flow reduction in CAD was assessed using the virtuQ™ software package ( 13 ). The study was approved by Regional Ethics Committees (16/NW/0897 and 08/H1308/193) and informed consent was obtained.…”
Section: Methodsmentioning
confidence: 99%